Dissolving microneedle integrated with benidipine loaded ethosomes for transdermal delivery - AL-Japairai, Khater Ahmed Saeed; Almurisi, Samah Hamed; Nadiya, Abdul-Halim; Syed Mahmood, . (Elsevier, 2024)
Benidipine HCl (BEN) is a drug used for the treatment of hypertension. However, this drug suffers from low oral bioavailability. This study introduces a novel approach to address this issue by developing BEN-loaded ethosomes (BEN-E) that integrate into dissolving microneedles for transdermal delivery. The BEN-E was prepared using a rotary evaporation method and optimised using the Box-Behnken design. Following that, the optimised BEN-E formulation was integrated into dissolving microneedles (DMNs). The optimised lipid vesicles selected comprised lipoid S75 (339.66 mg), ethanol (34.51 %), and sonication time (70 s) and showed a vesicle size of 149.4 ± 3.81 nm, an EE% of 88.57 ± 0.38 %, and a transdermal flux of 19.12 ± 0.19 μg/cm²/hr. On the other hand, the resulting BEN-E-DMNs exhibited sharp pyramidal microneedles, sufficient mechanical strength, good insertion capability, and fast dissolution in rat skin. In the ex vivo study, the permeation coefficient of BEN was significantly improved by BEN-E-DMNs compared with optimised BEN-E and BEN-DMNs. The pharmacokinetic studies showed that the BEN-E-DMNs had a Cmax of about 0.698 ± 0.037 μg/mL and an AUC₀₋ₜ of about 15.821 ± 0.868 μg/hr/mL. Moreover, it improved the relative bioavailability of BEN by about 1.58 times compared to the orally marketed BEN tablet and about 2.95 times compared to the BEN-DMNs. In conclusion, the ethosomes combined with dissolving microneedles have shown high potential as carriers for the transdermal delivery of BEN.